(untitled) (Marketing Journal, 2025)
This article explores the impact of emotional marketing on consumer behavior in the digital environment. It demonstrates that an emotional approach enhances user engagement, improves brand recall, and fosters loyalty. The study examines the potential of te chnologies, including artificial intelligence and social media, as well as issues related to the ethical use of data. The results confirm that integrating emotional № 1 273 marketing with digital tools increases the effectiveness of advertising campaigns. And the impact of emotional stimuli on humans, including color, music, and scent.